Effect of sewage sludge and nitrogen in the nutrition and initial development of castorbean - Backes, Clarice [UNESP]; de Lima, Claudinei Paulo [UNESP]; Fernandes, Dirceu Maximino [UNESP]; de Godoy, Leandro José Grava [UNESP]; Kiihl, Tammy Aparecida Manabe; Villas Bôas, Roberto Lyra [UNESP] (My University, 2009)
Aiming to evaluate the application effect of different sewage sludge (SS) doses, with and without nitrogen addition, in the castorbean initial development, one experiment was installed in an entirely randomized experimental design, in split-plot scheme 5 X 2, constituted of five sewage sludge doses (0, 4, 8, 16 e 32 Mg ha-1) and nitrogen addition or not (15 kg ha-1), with five replications. The experimental unit was constituted of plastic bags with capacity of 3,5 dm3 of soil. Fifty days after emergency it was evaluated height of plants, dry matter of the aerial part, nutrient content in the aerial part, soil electrical conductivity and soil chemical analysis. The SS doses promoted increase in the height of plants and dry matter of castorbean. The concentration of N, K, Mg and S and also the micronutrients Cu, Fe, Mn and Zn in the aerial part of the plants also suffered a positive effect with SS doses, the same didn't occur for the P and Ca concentrations. N addition increased the concentration of N, S, Cu and Zn in the plants. The SS did not present significant effect over pH levels, phosphorous, potassium, calcium, magnesium, organic matter and soil cation exchange capacity after the experiment conduction period.
Efeito do lodo de esgoto e nitrogênio na nutrição e desenvolvimento inicial da mamoneira
Keywords: Nitrogen fertilization; Ricinus communis L.; Sewage sludge application